PERBANDINGAN KANDUNGAN LOGAM BERAT (Cu, Fe dan Zn) PADA AIR SUNGAI SIAK SEBELUM DAN SESUDAH PROSES PENJERNIHAN - Rutmayanti Pandiangan; Sugianto '; Usman Malik (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Comparison  of heavy metal  (Cu,  Fe  and  Zn)  content of Siak  river water  between before and after purification process has been done using an experimental method. The processstarted  by taking  sample of  the Siak River  water  at a distance of  1  meter  from  waste sewage system  of  rubber  manufacturing industry  PT.RICRY  Pekanbaru.  Concentration of pre-filtered  samples  was measured by  atomic absorption  spectrophotometer  (AAS), then each sample  was  filtered five times.  The result of pre-filtered samples characterized by  (AAS) of  Cu,  Fe  and  Zn  were  0.3809  ppm,  0.0051  ppm,  and  -0.0012 ppm.  The absorption percentage  of samples  characterized by  (AAS) for Fe, Zn and Cu were 12,02 %, 33,33 % and 72,54 %,  respetively (type I) and 33,15 %, 2,70 % and 80,39 % respetively for type II.  Based on the  obtained data,  it was concluded  that  the purity instrument  of  type I  was better  than  type II  for  water treatment.